2018
DOI: 10.1088/1674-1056/27/6/064301
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of acoustic waves in a fluid-filled pipe with periodic elastic Helmholtz resonators

Abstract: Helmholtz resonators are widely used to reduce noise in a fluid-filled pipe system. It is a challenge to obtain lowfrequency and broadband attenuation with a small sized cavity. In this paper, the propagation of acoustic waves in a fluid-filled pipe system with periodic elastic Helmholtz resonators is studied theoretically. The resonance frequency and sound transmission loss of one unit are analyzed to validate the correctness of simplified acoustic impedance. The band structure of infinite periodic cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Helmholtz resonators take advantage of the resonance characteristics of air, and they have good advantages in light weight and low frequency design only by structural design without additional In 2018, Yu et al [40] changed the rigidity of Helmholtz resonators (HRs) and designed a tube with a periodically arranged elastic HR (see Figure 10). Their research found that for a single Helmholtz cavity unit of the same size, the resonant frequency of the elastic HR is much lower than that of the rigid HR.…”
Section: Crystals 2020 10 X For Peer Review 7 Of 26mentioning
confidence: 99%
“…Helmholtz resonators take advantage of the resonance characteristics of air, and they have good advantages in light weight and low frequency design only by structural design without additional In 2018, Yu et al [40] changed the rigidity of Helmholtz resonators (HRs) and designed a tube with a periodically arranged elastic HR (see Figure 10). Their research found that for a single Helmholtz cavity unit of the same size, the resonant frequency of the elastic HR is much lower than that of the rigid HR.…”
Section: Crystals 2020 10 X For Peer Review 7 Of 26mentioning
confidence: 99%
“…[1−4] Researchers have paid a great deal of attention to effect of a flow on acoustic properties of duct systems loaded with HRs, due to the significance of flow effect in many engineering applications. [5,6] Experimental and empirical investigations of a mean flow on transmission loss of a single HR have been studied for a long time. Meyer et al investigated the effect of a flow on the acoustic impedance of an HR.…”
Section: (Received 18 September 2019)mentioning
confidence: 99%
“…resonator, and side-branch resonator (SBR) are notable in terms of narrow low-frequency sound attenuation due to their inherent acoustic properties [6,7]. But a bulky size is necessary which limits their practical applications.…”
Section: Introductionmentioning
confidence: 99%